Iron status and hepcidin response to a seven day training period of running or cycling - Sim, M.; Dawson, B.; Landers, G.; Tjalsma, H.; Swinkels, D.; Trinder, D.; Peeling, P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Exercise stimulates the production of the iron regulatory hormone hepcidin, causing peak levels 3 h post-exercise (Peeling et al., 2009). Such events may decrease iron absorption and recycling (Nemeth et al., 2004). However, non-weight-bearing exercise (cycling) was previously shown to reduce hemolysis (Telford et al., 2003) and interleukin-6 levels (Nieman et al., 1998) in comparison to weightbearing activity (running). To date, most studies have examined the acute post-exercise hepcidin response using weight-bearing exercise. Additionally, the impact of cumulative exercise sessions on hepcidin production remains unknown. This investigation compared the impact of an extended period of running vs. cycling on hepcidin levels and iron status. Methods: Ten active males performed two separate training blocks, performing either running (RTB) or cycling (CTB). Each block comprised 5 training sessions (Day [D] 1, 2, 4, 5, 6), performed over 7 days and matched for exercise intensity. Basal venous blood was obtained on D1, and on Recovery Days 3 (R3) and 7 (R7) to assess iron status, while basal and 3 h post-exercise urinary hepcidin levels were measured on exercise D1, D2 and D6, as well as R3 and R7 (basal levels only) for each training mode. Results: In RTB, basal urinary hepcidin levels were significantly elevated (p<0.05) at D2, R3 and R7 as compared to D1. 3 h post-exercise urinary hepcidin levels on D1 were also significantly higher in RTB compared to CTB (p<0.05). In CTB, large effect sizes suggested basal hepcidin levels were higher at R7 (d=1.26) compared to D1. Iron parameters were not significantly different at D1 compared to R3 and R7 during both training modes. Conclusion: Basal hepcidin levels may increase over an extended training program, especially if weight-bearing exercise is undertaken. In comparison, the reduced hemolysis typically associated with cycling may require more training sessions, or sessions of extended duration, before any changes in basal hepcidin levels appear. Chronically elevated hepcidin levels may help explain the high incidence of iron deficiency in athletes.